PENGARUH TAMBAK SILVOFISHERY TERHADAP SIFAT FISIK TANAH MANGROVE SEBAGAI LAHAN KONSERVASI DAERAH MUARA SUNGAI BOGOWONTO KULON PROGO DAERAH ISTIMEWA YOGYAKARTA - Faezatiy, Lulu'Ayu; Mulyanto, Djoko; Nurcholis, Mohammad (Jurnal Tanah dan Sumberdaya Lahan, 2024)
The Bogowonto River estuary is a coastal area in the open water category because it faces the Indian Ocean directly, it has high wave energy, which will cause erosion and abrasion, and the presence of mangrove and pond ecosystems (silvofishery) can support the development of coastal areas as conservation land. So it is necessary to conduct research to examine the influence of soil physical properties on silvofishing and determine the types of mangroves in the Bogowonto River estuary area. The method used was a survey, where soil samples were tested at the Yogyakarta BPTP Laboratory and the Yogyakarta "Veteran" National Development University at a depth of 0–20 cm and 20–40 cm. Sampling was conducted in a zigzag method from the left (near the pond) and right sides of the river. The results of the research found that there are 2 types of mangroves, namely the Tan cang (Bruguiera sp.), which grows far from the coastline and close to fish pond areas (silvofishery), has a has a relatively stable pH, is dominated by clay texture, and has a low salinity level. White Mangrove (Avicennia sp.) grows near the coastline, with a dominant sandy loam texture, low-normal pH, and high salinity levels. Mangroves that grow along the southern river in the presence of silvofishery can help with the deposition process of mud that is transported along the river and maintain the sustainability of fish populations, and litter from mangroves tends to increase the organic matter content of the soil.